Express the following in simplified radical form. \[ \sqrt{x y^{3}} \sqrt[3]{x^{2} y} \]
Real Tutor Solution
Answer
Solution
Reviewed and approved by the UpStudy tutoring team
Beyond the Answer
To simplify the expression \(\sqrt{x y^{3}} \sqrt[3]{x^{2} y}\), we can start by breaking down each radical term into simpler components. 1. Rewrite the square root and cube root using exponent notation: \[ \sqrt{xy^3} = (xy^3)^{1/2} = x^{1/2} y^{3/2} \] \[ \sqrt[3]{x^2 y} = (x^2 y)^{1/3} = x^{2/3} y^{1/3} \] 2. Now, we can multiply the two expressions: \[ \sqrt{xy^3} \cdot \sqrt[3]{x^2 y} = (x^{1/2} y^{3/2})(x^{2/3} y^{1/3}) \] 3. Using the property of exponents that states \(a^m \cdot a^n = a^{m+n}\), we combine the like bases: \[ x^{1/2 + 2/3} y^{3/2 + 1/3} \] 4. To add the exponents, we need a common denominator. The least common multiple of 2 and 3 is 6: - For \(1/2\), convert to sixths: \(1/2 = 3/6\) - For \(2/3\), convert to sixths: \(2/3 = 4/6\) - Thus, \(1/2 + 2/3 = 3/6 + 4/6 = 7/6\) - Similarly, for \(3/2\) and \(1/3\): - \(3/2 = 9/6\) - \(1/3 = 2/6\) - Thus, \(3/2 + 1/3 = 9/6 + 2/6 = 11/6\) So our expression now looks like this: \[ x^{7/6} y^{11/6} \] Now, we can express it in radical form. Recall that \(x^{a/b} = \sqrt[b]{x^a}\): \[ = \frac{\sqrt[6]{x^7} \cdot \sqrt[6]{y^{11}}}{1} \] This gives us: \[ \frac{\sqrt[6]{x^7 y^{11}}}{1} = \sqrt[6]{x^7 y^{11}} \] Thus, the simplified radical form of the given expression is: \[ \sqrt[6]{x^7 y^{11}} \]